The effectiveness of cooperative learning strategies and its’ impact on improving academic performance of UTAR Undergraduates - Foong, Joo Yee (2021)
This action research took place among 60 English Education undergraduates from Universiti Tunku Abdul Rahman in Kampar campus. Unlike other research, this research involved both researcher and samples in the study. In this research, researcher implemented cooperative learning strategies in solving the issues of poor academic achievement in a classroom. The researcher used two types of cooperative learning strategies, namely Student Teams Achievement Divisions (STAD) and Think Pair Share (TPS) to analyse the effectiveness of each strategy on improving students’ academic achievement. Throughout the study, researcher collected data based on scores obtained by both experimental and control groups in pre-test and post-test. Next, researcher further identified the perception of students on the implementation of cooperative learning strategies in ESL classroom through interview session. Based on the findings, the researcher concluded both cooperative learning strategies were impactful on improving the academic performance, and STAD was the most effective one. Besides, these cooperative learning strategies engaged students to interact actively, think critically, feel motivated and develop interpersonal skills. However, the downside of this research was the unfamiliarity of student towards these learning strategies and the practice of individualistic during the online lesson.